(3bWYI ef GdMOGFbs - (3GdOQGRj, GdHMQGfj, GHf YUahQ, jhSa Hf CMeO Hf EHQGgje, J(B1186(3g`s ((3Nda Hf YScQs)
(3ChdgG (B:s
(3ddWgGQI hEfeG MUd dg HGdWgGQI EHGMI GdUdGI NGUI hPHdc jXgQ GdaQb HjfgeG HGdfSHI Edi GdWgGQI(B...s
(3BNQgG (B:s
(3Pdc Cf GdeUdj dG jSJWjY Cf jQO GdSdGe dCf GdJSdje ef GdeSde JWhY hGdQO Ydjg aQjVI (B... (3Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B8(3, U(B215s
(3GdPQjYI HQbe(B: 1557s
(3GdCYdGe(B: (3L(B8(3, U(B215s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis